PENINGKATAN AKTIVITAS DAN HASIL BELAJAR IPS MELALUI PENERAPAN METODE PEMBELAJARAN JIGSAW PADA SISWA KELAS VIII B SEMESTER II S M P NEGERI 9 SURAKARTA TAHUN PELAJARAN 2015 / 2016 - Suparni, Suparni (Jurnal Pendidikan Ilmu Sosial, 2016)
The aim of this research was to improve the student’s activeness and learning outcome of social science subject in the understanding of Indonesian independence struggle through Jigsaw method implementation. The respondents were the students of grade VIII class B at SMP N 9 (State Junior High School 9) Surakarta. The data collection was conducted by interview, documentation, and questionnaire. The research used the interactive technique which was divided into three steps. The steps were, firstly data reduction, secondly data presentation, and thirdly concluding. Before the first cycle of this action research, there were 5 students with low learning activity and 10 students with low learning outcome. The result of the first cycle was the student’s activeness and learning outcome increase 15,62 % or 5 students improved their activeness and learning outcome. In the second cycle, almost all students had high activeness and learning outcome. Therefore, the implementation of Jig Saw method was successful to improve student’s activeness and learning outcomeKeywords: Learning Outcome, Activity, Jigsaw